E-pet service apps for Kampar residential mobile application - Lim, Chun Keat (2024)
In this mobile application project, I've developed a mobile application for e-pet services, specifically tailored to meet the needs of Kampar residents. The primary goal of this application is to deal with the challenges associated with traditional methods of booking pet services. The goal is to streamline the process of reserving pet services, ensuring it is convenient and efficient for users while offering flexibility to accommodate diverse needs. Within the scope of this project, three key problem statements have been identified. Firstly, the current e-pet service application offers a limited range of services, potentially constraining its user base. Thus, a primary objective is to expand the range of services offered to include essential pet care services. By diversifying the services available, the aim is to better cater to the needs of pet owners and differentiate the application from competitors. Secondly, a significant challenge lies in the lack of trust among pet owners, leading to a loss of market share and difficulties in building brand reputation. To address this challenge, the project focuses on implementing robust verification systems for service providers and establishing transparent rating and review mechanisms to instill confidence in users. Thirdly, scheduling inflexibility contributes to high rates of no-shows and lastminute cancellations, often due to the absence of timely reminders. To mitigate this issue, a comprehensive booking reminder and confirmation system is being implemented. This system will send reminders with options for users to confirm or cancel appointments, aiming to reduce missed appointments and enhance overall efficiency and customer satisfaction. Through these initiatives, the aim of this personal project is to revolutionize the pet services landscape in Kampar. The objective is to develop an easy to use and effective platform that meets the diverse needs of pet owners while fostering user loyalty and satisfaction. By addressing the identified problems and aligning project objectives with the needs of the target audience, the goal is to establish a trusted and reliable solution for pet care in Kampar.